O impacto das notícias no mercado financeiro brasileiro - Faustino, Caio César Ribeiro (2013)
The information published in the media helps investors in decision-making process and therefore influences the financial market. The purpose of this study is to explore the effect of publishing news in the financial market. To achieve this, the paper discusses variables as amount of news and the semantic effect of each of them as well as their relation to rates of return, volatility and the trading volume from Ibovespa. The hypotheses of the research are that the amount of published content and the sentiment of information may be valid predictors for the level of volatility, return and volume. However, this does not imply that this data can help to predict the future, but surely the present. The results have revealed that the amount and semantic content of the news have no significant effect on the return, but increases in the amount of news and in the amount of negative news suggest the increase in volatility and trading volume of Ibovespa. Furthermore, the effect of news is greater in volatility according to the state of the economy, namely the impact of bad news are larger in good times than in bad times. This paper also provides further evidence for the effect according to the days of the week. That is, the amount of news published on Friday through Sunday is related to the volatility and trading volume of Ibovespa.